Conceptualizing ethnicity and nation building in Malaysia: A lesson from Nigeria - Ibrahim, Yahya Saleh; Halliru, Tijjani (Institute of Tun Dr. Mahathir Mohamad’s Thoughts, Universiti Utara Malaysia, 2010)
Conflict of ethnic origin keep presenting its ugly consequences to most of the developing and developed societies, with no much lessons learned. This ethnic conflicts usually starts with a mere complain or grievance that is most of the time ignored, this minor issues if not well tackled could metamorphosed into a widespread genocides, killings, maiming, destruction of valuable properties or in a form of social vices, like addiction, armed robbery, prostitution and host of other vices. Hence this paper presents a catalogue of the various ethnic confl icts that occurred in Nigeria from 1999-2002, immediately after the coming up of a democratically elected government in the country. The paper concluded that, the unassuming right provided by the Nigeria democracy might have contributed to the escalation of the conflicts, that has direct relationship with ethnicity. It also presumed that, the conflicts may also be associated with long military dictatorship in the country, which likely socialised the citizens to learn the act of intolerance, hostility and the act of violence. The lessons drawn from Nigeria experience were married with the recent happening in Malaysia, so that it will serve as a lesson to Malaysia to act fast not to allow its issue degenerates to an uncontrollable stage. This paper, therefore, make use of documented records from both official documents and eyewitnesses records to generates all its data and argument for this presentation. “Tribalism is the bane of independent Africa...There are 2,000 language Groups of which 50 are prominent, and countless more subdivisions of tribe and clan.This complex heritage has been only slightly eroded by inter-marriage and the drift to the cities. Nor have the eff orts of African leaders to impose a national identity on their diverse peoples, assembled within borders inherited from colonial days, worked well. African state builders tread a narrow path between the fact of tribal loyalties and the need to minimize inter-tribal hostility.” “Tribalism in Africa,” The Economist (September 10, 1994), pp. 46, 48.